2016
DOI: 10.1039/c6ee00612d
|View full text |Cite
|
Sign up to set email alerts
|

Achieving long-term stable perovskite solar cells via ion neutralization

Abstract: Corrosive ionic defects in perovskite films degrade perovskite solar cells (PSCs) and long-term stable PSCs are realized by neutralizing the defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
218
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(221 citation statements)
references
References 33 publications
3
218
0
Order By: Relevance
“…2(b)). 55 Greater electrode stability could also be achieved by Guerrero et al by moving away from using either Ag or Al, and instead employing a Cr 2 O 3 /Cr electrode which is shown to be chemically inert towards iodide. 58 Similarly, Au electrodes do not undergo any corrosion; however, the price of the metal is prohibitively high for large-scale commercialization.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…2(b)). 55 Greater electrode stability could also be achieved by Guerrero et al by moving away from using either Ag or Al, and instead employing a Cr 2 O 3 /Cr electrode which is shown to be chemically inert towards iodide. 58 Similarly, Au electrodes do not undergo any corrosion; however, the price of the metal is prohibitively high for large-scale commercialization.…”
mentioning
confidence: 97%
“…However, several studies have shown that another source for device impairment is chemical reactions between the iodide ions from the perovskite and the metal electrode, typically Ag or Al. [55][56][57][58] This can result in the formation of an insulating barrier such as Ag- which will impair charge extraction at this electrode. 59 Long-term operability of these devices requires therefore, that, additionally to moisture ingress from the outside, the diffusion of ions from the perovskite to the electrode is blocked in order to avoid electrode corrosion.…”
mentioning
confidence: 99%
“…[133] With the NiMgLiO-based HTM, a large-size (1.02 cm 2 ) planar p-i-n perovskite solar cell with an efficiency of up to 16.2% was achieved. Back et al developed a new concept of a chemical inhibition layer in PVSCs by using amine-mediated metal oxide (AM-TiO x ) between PCBM and Ag electrode, [134] which can successfully protect the Ag electrodes by extracting and stabilizing the ionic defects migrating from the perovskite layer, thereby realizing planar p-i-n PVSCs with long-term stability. ZnO was also used for optimizing the contact properties of the PCBM/Ag interface.…”
Section: Inorganic Metal Oxidesmentioning
confidence: 99%
“…Many people reported that the introduction of interfacial materials containing amine groups at the ETM/Ag electrode interface could neutralize the migrating iodide ions and inhibit the formation of the insulating Ag-I bonds on the surface of the Ag electrode, resulting in highly stable PVSC devices. [134,150] Another solution is replacing Ag electrodes to other stable metals. Copper (Cu) may be an ideal electrode material, which is stable even in direct contact with perovskite for many years, and there is no notable diffusion of Cu into the perovskite.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…Metal-organic hybrid perovskite solar cells have been extensively studied by many researchers all over the world and its power conversion efficiency (PCE) reaches over 20%, recently [1][2][3]. The fabrication methods of perovskite film are classified mainly into two method: one is a solution growth method from precursor solutions of PbI2 and MAI or their mixed solution by a spincoating technique, and another is a vapour growth method by conversion of perovskite phase from PbI2 films by annealing under methyl ammonium iodide (MAI) vapour.…”
Section: Introductionmentioning
confidence: 99%